Linkage modification of a zinc oxide photoelectrode prepared with polyethylene glycol for electron transport improvement in dye-sensitized solar cells - Sutthipoj Wongrerkdee (2020)
© Indian Academy of Sciences. The purpose of this study is to synthesize ZnO aggregate films using simple precipitation with polymer modification for linkage improvement of the ZnO photoelectrode. The starting materials of zinc acetate solution and ammonia solution were mixed under violent stirring conditions. A portion of the polymer (polyethylene glycol) was slowly added into the mixed solution to obtain the viscous ZnO precursor. The precursor was then coated onto a fluorine-doped tin oxide substrate and annealed to form ZnO films. The scanning electron microscopy results revealed the formation of ZnO aggregates with flower-likemicrostructures. The appearance of Zn and O elements indicated a fair ZnO formation. The X-ray diffraction patterns and Raman shift confirmed the hexagonal wurtzite crystal structure of the ZnO aggregates. For dye-sensitized solar cell (DSSC) application, power conversion efficiency was enhanced because of the improved photovoltaic characteristics including the open-circuit voltage, fill factor, series resistance, shunt resistances and recombination resistance, perhaps, due to the large particle size of the ZnO aggregates and their flower-like microstructures. The flower-like microstructure likely acts as a bridge to link each ZnO particle. The flower-like microstructure plays the role of an express pathway in electron transport in the DSSC. Therefore, the ZnO aggregation with a flower-like microstructure has the potential to improve the electron transport for efficiency enhancement of a DSSC.